Definitionsteori. En filosofisk og terminologisk tilgang til definitionsteoretiske problemstillinger - Olesen, Charlotte (HERMES - Journal of Language and Communication in Business, 2002)
The present paper analyses the theoretical-definitional problems that combine philosophy and LSP-translation. During the last 20 years alternative terminological meta-theories have seen the light of day, criticising the classical terminology’s insistence on contextual independence, uniqueness of reference and standardisation. The article will describe the philosophers and the theories of science that have inspired the classical as well as the new, alternative terminological theories and analyse the impact that the meta-theories within these two movements may have on terminological methodology and conceptual analysis.